MANAJEMEN KEUANGAN DESA DI DESA TOMPASO II KECAMATAN TOMPASO KABUPATEN MINAHASA - RORIMPANDEY, CHRISTOFEL; OGOTAN, MARTHA; LONDA, VERY (Sam Ratulangi University, 2019)
In the Minister of Home Affairs Regulation Number 20 Year 2018 concerning Village FinancialManagement, it is stated that village finance is all village rights and obligations that can be valued withmoney and everything in the form of money and goods related to the implementation of village rights andobligations. The purpose of this study was to find out the village financial management in Tompaso VillageII, Tompaso Subdistrict, Minahasa District. The method of approach that is suitable for use in this study isa qualitative method. Data collection techniques used were interviews, observation and documentaries.Based on the results of the research and discussion, the authors draw conclusions regarding VillageFinancial Management in Tompaso II Village, Tompaso Subdistrict, Minahasa District, seen from the fourstages of the government financial management cycle, namely: (1) Planning and Preparation (2)Ratification, (3) Implementation, ( 4) Reporting and evaluation. Suggestions that can be given are Planningand Preparation, Ratification, Implementation of the Village APB needs to be improved in quality and APBVillage Reporting and Evaluation should be truly in accordance with the facts.Keywords: Management, Finance, Village.